(untitled) (Journal of Asian Geography, 2022)
Temperature is the primary weather element that determines the other weather element in a place. The Northern region of Sri Lanka has different climatic conditions that clearly define summer and winter because of its geographical setup. The area is categorized under the dry zone because of its climatic condition. However, the Northern region has unique characteristics compared with the other areas of the dry zone. This study aims to identify the changes in the temperature pattern of Northern Sri Lanka based on monthly, seasonal, and annual temperature data. The data were obtained from various sources, such as the meteorology department. The Mann Kendal (M.K.) trend and Sen’s slope estimator analysis were employed to study the data. According to the M.K. analysis, there is a positive trend in the annual temperature pattern in all five stations, such as Thirunelvely, Iranaimadu, Murungan, Vavuniya, and Kanukkerny, and Sen’s values of these stations show the increase in temperature in the study area. The minimum and maximum temperature of the annual pattern indicate a significant increase in the study area. Further compared to the 1930 to 1960 climatic period, the current climatic period (1990 to 2020) has a 0.84°C increase in the study area. Additionally, there are increases in the study area’s monthly temperature pattern, especially in July, which significantly increases in the study area. An appropriate mitigation and adaptation action would help the sustainable development of the Northern region of Sri Lanka.